Football nightmare - Hirschfeld, Robert; Hirschfeld Robert (Boston : Little, Brown, 2001)
Having dropped a pass and made his football team miss having an undefeated season, thirteen-year-old Keith fears that he will continue to make bad mistakes and wonders if he should continue playing football.
Keywords: Football; Fear